The Impact of Macroeconomics Factors on the Jakarta Composite Index - Hartini Pop Koapaha (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to assess the relationship between macroeconomics factors on the Jakarta Composite Index. The multiple linear regression is employed to examine the impact of four macroeconomics variables namely GDP growth, inflation, interest rate spread, and broad money (money supply) on the Jakarta Composite Index. The result presents that Jakarta Composite Index is negatively affected by inflation and interest rates, while the increase in money supply boost the Jakarta Composite Index. In this study GDP growth has no significant influence on the Jakarta Composite Index. Investors may take advantage of this circumstance, notably they can purchase blue chips when inflation and interest rates rise and sell their shares when the money supply is expanding.